2022
DOI: 10.1007/s13399-022-02518-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of three kinds of extraction kinetic models of crude polysaccharides from Codonopsis pilosula and evaluate the characteristics of crude polysaccharides

Abstract: In this study, the second-order model, Fick’s second law of diffusion, and the Peleg model were used to evaluate the extraction kinetic model of polysaccharide (CPP) from Codonopsis pilosula . The characteristic functional groups, surface structure, and physical and chemical properties of CPP were analyzed by multi-spectroscopic and microscopic techniques. The results showed that the extraction process agreed well with the second-order model, Fick’s second diffusion law, and Peleg model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Makanjuola et al [ 40 ] reported that the phenolic content and antioxidant properties in ground tea with particle sizes of 0.425 mm were higher than those in ground tea with particle sizes of 1.180 mm. A rapid increase in polysaccharide yield was observed when the particle size of Codonopsis pilosula powder decreased from 420 to 180 μ m, and the optimal particle size was 180 μ m; the maximum polysaccharide yield was 15.56% [ 41 ]. In contrast, catechin content and antioxidant properties in hydroalcoholic extracts of green tea decreased for particles of sizes less than 50 μ m, showing that the smallest particles can sediment and decrease the contact between particles and the extraction solvent, thereby reducing mass transfer efficiency [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Makanjuola et al [ 40 ] reported that the phenolic content and antioxidant properties in ground tea with particle sizes of 0.425 mm were higher than those in ground tea with particle sizes of 1.180 mm. A rapid increase in polysaccharide yield was observed when the particle size of Codonopsis pilosula powder decreased from 420 to 180 μ m, and the optimal particle size was 180 μ m; the maximum polysaccharide yield was 15.56% [ 41 ]. In contrast, catechin content and antioxidant properties in hydroalcoholic extracts of green tea decreased for particles of sizes less than 50 μ m, showing that the smallest particles can sediment and decrease the contact between particles and the extraction solvent, thereby reducing mass transfer efficiency [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to expressions derived from Fick's law, the adapted second-order rate law has also been employed for extraction modeling (Jabar et al, 2015;Wang et al, 2022). A distinct extraction kinetic for microwave-assisted processes has been highlighted by another report (Lee et al, 2016), owing to its significant increase in the obtained extraction yields at a reduced time as compared to the conventional extraction method.…”
Section: Extraction Kinetic Modellingmentioning
confidence: 99%
“…Originally, Peleg’s kinetic model was meant to describe the absorption processes. However, due to a similar asymptotic shape of the sorption and extraction kinetic curves, this modeling was widely applied for the description of the extraction curves (e.g., analysis of the extracted matter over time) of bioactive substances from plants [ 23 , 24 ]. PPT quantification in the juniper leaf extracts was carried out using HRMS/MS detection.…”
Section: Introductionmentioning
confidence: 99%